ANALISIS POLA PIKIR DAN PERILAKU LINGKUNGAN MAHASISWA PROGRAM STUDI PENDIDIKAN FISIKA FKIP UNRI TERHADAP LINGKUNGAN HIDUP DI KAMPUS FKIP UNRI - Muhammad Syafii (Jurnal Pendidikan, 2018)
This study aims to: (i) to determine the extent of mindset and environmentalbehavior students Physics Education Study Program FKIP towards the environment in the RiauUniversity Teaching and Education Faculty (FKIP); (ii) to test / analyze whether there is arelationship between gender, mindset and environmental care behavior Physics Educationstudents at the FKIP UNRI Campus. From the results of the study, it was found that the mindsetand behavior Physics Education students towards environmental concerns in FKIP UNRICampus, as follows: (i) the majority of respondents or 50-58% of respondents had a good scoreabout environmental mindset; (ii) there are 53% -65% of respondents aware that respondents arewrong in maintaining the quality of the environment (iii) environmental awareness is still low,as evidenced by the respondents' answers, where the answer is rarely involved (JT) is the most common answer, as evidenced by the number of scores (40-53%). From the results of testing therelationship between sex variables, with the mindset and behavior of students of physicaleducation study program FKIP Unri towards the environment at the Unri FKIP campus, it wasconcluded that: (i) Gender is not related to mindset and behavior about the environment, sex isnot also related with concern for the quality of the FKIP Unri Campus environment; (ii) mindsetrelated to the behavior of students of the Faculty Physical Education FKIP Unri , the mindset isalso related to concern for maintaining environmental quality.